Analysis of the Efficiency Level of Islamic Commercial Banks in Indonesia using the Stochastic Frontier Analysis (SFA) Method for the 2021-2023 Period - Syifa Sakina Ahdanissa; Hilendri, Baiq Anggun (International Journal of Business and Applied Economics, 2024)
This study aims to determine the efficiency level of Islamic Commercial Banks (BUS), especially at Regional Government Islamic Commercial Banks and National Private Islamic Commercial Banks in Indonesia for the 2021-2023 period, using the Stochastic Frontier Analysis (SFA) method. This research is a quantitative study with panel data and secondary data used, namely third-party funds, total assets, labor costs, and financing. The results of this study indicate that the efficiency level of the Regional Government BUS is 0.9757 and the National Private BUS is 0.95451. This shows that each Bank is efficient and performs its intermediary function well. Therefore, there is no significant difference between the efficiency of Regional Government BUS and National Private BUS with the Mann Whitney U-Test difference test.